Low Plasma ADAMTS13 Activity Is Associated with Coagulopathy, Endothelial Cell Damage and Mortality after Severe Paediatric Trauma - Russell, Robert T.; McDaniel, Jenny K.; Cao, Wenjing; Shroyer, Michelle; Wagener, Brant M.; Zheng, X. Long; Pittet, Jean-François (Thrombosis and Haemostasis, 2018)
Decrease of plasma activity of ADAMTS13, a metalloenzyme that cleaves von Willebrand factor (VWF) and prevents adhesion and aggregation of platelets, has been reported early after onset of systemic inflammation resulting from infections and after severe trauma. Here, we determined whether trauma-induced systemic (sterile) inflammation would be associated with a reduction of plasma ADAMTS13 activity in paediatric patients and its association with disease severity and outcome. Paediatric patients (n = 106) with severe trauma at a level 1 paediatric trauma centre between 2014 and 2016 were prospectively enrolled. Blood samples were collected upon arrival and at 24 hours and analysed for plasma levels of ADAMTS13 activity, VWF antigen, collagen binding activity, human neutrophil peptides (HNP) 1–3, coagulation abnormalities, endothelial glycocalyx damage and clinical outcome. Plasma samples were also collected for similar measurements from 52 healthy paediatric controls who underwent elective minor surgery. The median age of patients was 9 years with 81% sustaining blunt trauma. The median injury severity score was 22 and the mortality rate was 11%. Plasma levels of ADAMTS13 activity were significantly lower and plasma levels of VWF antigen and HNP 1–3 proteins were significantly higher for paediatric trauma patients on admission and at 24 hours when compared with controls. Finally, the lowest plasma ADAMTS13 activity was found in patients who died from their injuries. We conclude that relative plasma deficiency of ADAMTS13 activity may be associated with more severe traumatic injury, significant endothelial glycocalyx damage, coagulation abnormalities and mortality after severe trauma in paediatric patients.
Keywords: paediatric; trauma; injury; coagulopathy; ADAMTS13; von Willebrand Factor; human neutrophil peptide